Helge S. Kvanvig, Primeval History: Babylonian, Biblical, and Enochic. An Intertextual Reading (Supplements to the Journal for the Study of Judaism 148; Leiden: Brill, 2011). Pp. xvi, 610. € 184, 251. ISBN 978-90-04-16380-5 - Drawnel, Henryk (The Biblical Annals, 2015)
Book review: Helge S. Kvanvig, Primeval History: Babylonian, Biblical, and Enochic. An Intertextual Reading (Supplements to the Journal for the Study of Judaism 148; Leiden: Brill, 2011). Pp. xvi, 610. € 184, 251. ISBN 978-90-04-16380-5.